Design, Synthesis, and Analytical Evaluation of Fsp3‐Inspired Raman Probes for Cellular Imaging. Issue 30 (9th August 2022) - Steven, Craig F.; Lee, Martin; Nichol, Gary S.; Davey, Paul R. J.; Chiarparin, Elisabetta; Brunton, Valerie G.; Hulme, Alison N.
Abstract: The fraction of sp 3 ‐hybdrised carbons (Fsp 3 ) in drug candidates and other biologically relevant compounds has been proposed to be an important physicochemical consideration within medicinal chemistry. Currently available small‐molecule probes for Raman imaging are not optimised for biological applications. We sought to improve upon the highly Raman‐active, yet rigid, lipophilic, and aggregative, bisarylbutadiyne (BADY) motif by introducing Fsp 3 character. BADY analogues were designed, efficiently synthesised, and analysed by mass spectrometry – revealing a statistical correlation between compound aggregation and cLog P, but no correlation with Fsp 3 . However, X‐ray crystallography demonstrated that the modifications to the BADY structure had a marked effect on crystal packing, suggesting Fsp 3 may still be important in reducing intermolecular stacking, and thus aggregation, of BADY. Cellular imaging by stimulated Raman scattering (SRS) microscopy allowed comparison of the intracellular distribution of the tags, guiding the design of future Raman probes. Abstract : New tags have been developed for stimulated Raman scattering (SRS) cellular imaging with increased Fsp 3 character over existing alternatives. These diyne‐containing tags were synthesised by an efficient Pd‐catalysed cross‐coupling methodology and analysed by mass spectrometry (MS) association studies and X‐ray crystallography before imaging. MS data showed a linear relationship between aggregation and cLog P whilst X‐ray experiments suggested modifications had affected π‐π stacking.